FRI0411 A Cross Sectional Study of The Clinical and Ultrasound Entheseal Involvement in Patients with IBD. (15th July 2016) - Bertolini, E.; Macchioni, P.; Beltrami, M.; Bassi, F.; Marani, B.; Salvarani, C.; Catanoso, M.
Abstract : Background: Previous studies have reported the high prevalence of occult SpA in IBD patients. Objectives: To investigate the presence of clinical and ultrasound peripheral entheseal abnormalities in a consecutive series of IBD patients. Methods: 61 IBD consecutive patients [26 Crohn's disease (CD) and 35 ulcerative colitis (UC), M/F 32/29, mean age 35.7+12.4 years, mean disease duration 57+93 months] entered the study. Gastroenterological examination consisted of the determination of bowel involvement, extraintestinal manifestations, MAYO and CDAI score. A complete rheumatological examination which included 66 peripheral join count, MASES and Leeds entheseal evaluation, BASDAI, BASFI and evaluation of spine mobility was done at study entry. ESR and CRP were evaluated at study entry. US examination was done using an Esaote MyLabClass, 18–6MHz linear multifrequence transducer both in gary scale and with PD. The following enthesis were separately studied clinical and US by two rheumatologist unaware of the other evaluation: lateral elbow epicondyle, distal quadricipital insertion at the patella, proximal and distal patellar tendon insertions, Achilles tendon an plantar fascia insertion at the calcaneous. Knee and ankle joints were evaluated for synovial hyertrophy, PD signal and fluid. Extensor and flexor tendons of the foot and ankle were evalutaed for the presence of tendon sheat fluid, synovial hypertrophy and PD signal. Quadriceps, patellar, Achille and plantar fascia entheses were scored according to the 0–36 Glasgow Ultrasound Enthesitis Scoring System (GUESS) and power Doppler (PD). Correlations of GUESS and PD with IBD features [duration, type (CD/UC) and activity (disease activity index for CD/Truelove score for UC)] were investigated. Results: 29/61 (47.5%) patients had at leat one entheseal alteration at clinical examination and 56 (91.8%) presented almost one US entheseal abnormality with a mean 3.05±1.7 number of abnormal enthesis /patient. The mean MASEI was 11±9 and the mean GUESS 5.8±3.9 with 56/61 patients with value >1. The US evidence of enthesitis was higer in CD with ileo-colon localization as compared to ileo or colon involvement (100% vs 89% and 50%, p=0.03). Patients with disease duration >12 months have significantly grater number of cronical (2.48±1.5vs3.7±1.7, p=0.01) and acute enthseal alteration (3.0±1.3vs1.9±1.3, p=0.01) as compared with patients with disease duration <12 months. Conclusions: US entheseal abnormalities are present in a high percentage of IBD patients. US enthesopathy is associated with longer disease duration and topographical localization of gut disease. Disclosure of Interest: None declared